Iddah Sebagai Instrumen Perlindungan Perempuan Dalam Hukum Islam - Miftakur Rohman; Yuliana (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2024)
This research examines the concept of iddah in Islamic law, focusing on its provisions, criteria, and impact on the rights and welfare of Muslim women. Iddah is a waiting period that a woman must undergo after divorce or the death of her husband, which aims to ensure the certainty of lineage and allow time for emotional healing and social adjustment. This study analyzes the various provisions of iddah, such as the duration and conditions that must be met, as well as the criteria that affect the iddah period, such as age, state of pregnancy, and previous marital status. The impact of iddah on women's rights, including the right to maintenance during iddah (nafkah iddah) and the right to mut'ah, is also discussed in depth. The research also explores the psychological and social well-being of Muslim women during the iddah period, as well as the legal and social implications of its provisions in the modern context. Based on an analysis of classical Islamic law and contemporary practices in various countries, the study concludes that while iddah aims to protect women's rights, its implementation often presents challenges, particularly in relation to women's financial and emotional well-being. Therefore, legal reforms that take into account the current social context and women's needs are needed to ensure that iddah provisions can be applied fairly and provide maximum protection for Muslim women